A Diletto And His Storytellig Strategy - Patrocínio, Rachel Farias do; Figueiredo, Rafael; Souza, Juliana Lopes de Almeida (Archives of Business Research, 2017)
The strategy of involving consumers and prospects through tales or stories in advertising, known as storytelling, has been widely used by organizations and well accepted by the general public. One of the companies that bet on this format was the brazillian ice cream and popsicle maker, the Diletto brand. However, the strategy of storytelling used by the organization had a negative repercussion, because the story told was not exactly the real story about the beginning of the company. Thus, this article intends to identify the true reasons that made Diletto’s strategy detrimental to the brand. To that end, the paper tackled how a non-assertive storytelling strategy can compromise the organization’s image. The research identified, through data collection research and the theoretical basis of authors who are specialists in the subject, the factors that led to the failure of the strategy and why the negative repercussion involving the brand, after the true story became public knowledge.